Questions of the Analysis of the Economic Activity in the Work of Prof. Dimitar Dobrev - Ivanova, Rositsa (Research Papers, 2020)
Prof. Dr. Dimitar Dobrev is a distinguished Bulgarian scholar in the field of economic studies, the studies of independent economy, the accountancy and analysis of the economic activity. We can write a lot for Prof. Dobrev and his work.This publication makes a detailed study of the scientific work of Prof. Dobrev. The objective is to systematize the scientific contributions in his work and to outline his achievements in the theory and practice of the business analysis.In general, the contributions in the work of Prof. Dobrev may be systematized in the following areas: he makes comprehensive clarification of the questions about the nature of the economic activity; he develops the main questions of the studies of independent economy and scientifically proves the need to study its economics; he clarifies that the accountancy in its logical origin and historical development that allows him to outline and put the scientific foundations of the accountancy theory; he develops and puts the scientific foundations of the theory of balances; he makes the accountancy an important study discipline in the system of higher education in Bulgaria; he works for the establishment of the authority of the accounting specialists in Bulgaria; he develops the theory of the analysis of the economic activity on scientific bases.This publication highlights the views and contributions in the scientific work of Prof. Dobrev on different questions of the theory and practice of the economic activity analysis.
Keywords: Work; Views; Contributions; Analysis of economic activity; Dimitar Dobrev